A nationwide survey of hepatitis E viral infection in French blood donors. Issue 4 (26th February 2016) - Mansuy, Jean Michel; Gallian, Pierre; Dimeglio, Chloé; Saune, Karine; Arnaud, Catherine; Pelletier, Bertrand; Morel, Pascal; Legrand, Dominique; Tiberghien, Pierre; Izopet, Jacques
Abstract : Most cases of hepatitis E viral (HEV) infection in developed countries are autochthonous. Nevertheless, the reported seroprevalence of HEV varies greatly depending on the geographical area and the performance of the immunoassay used. We used validated assays to determine the prevalence of anti‐HEV immunoglobulin G (IgG) and IgM among 10, 569 French blood donors living in mainland France and three overseas areas. Epidemiological information was collected using a specific questionnaire. We found an overall IgG seroprevalence of 22.4% (8%‐86.4%) depending on the geographical area ( P < 0.001). The presence of anti‐HEV IgG was associated with increasing age ( P < 0.001) and eating pork meat ( P = 0.03), pork liver sausages ( P < 0.001), game meat ( P < 0.01), offal ( P < 0.001), and oysters ( P = 0.02). Conversely, drinking bottled water was associated with a lower rate of anti‐HEV IgG ( P = 0.02). Overall IgM seroprevalence was 1% (0%‐4.6%). The frequency of anti‐HEV IgM was higher in donors living in a high anti‐HEV IgG seroprevalence area (1.9% versus 0.7%, P < 0.001) and in those eating pork liver sausage (1.4% versus 0.7%, P < 0.01), pâté (1% versus 0.4, P = 0.04), and wild boar (1.3% versus 0.7%, P < 0.01). Conclusion: HEV is endemic in France and hyperendemic in some areas; eating habits alone cannot totally explain the exposure to HEV, and contaminated water could contribute to the epidemiology of HEV infection in France. (Hepatology 2016;63:1145–1154)